The Risk of Falls among Elderly at Panti Sosial Tresna Werdha Budi Luhur, Jambi City - Sari, Lisa Anita; Martawinarti, RTS Netisa (Sekolah Tinggi Ilmu Kesehatan Garuda Putih, 2025)
Elderly individuals are an age group that is vulnerable to various health problems, one of which is the risk of falling. Falls among the elderly can lead to injuries, decreased quality of life, and even death. Therefore, it is important to identify factors associated with the risk of falls, especially among older adults living in social care institutions such as nursing homes. This study aimed to describe the risk of falls among elderly residents at the Budi Luhur Social Institution for the Elderly (PSTW) in Jambi City. This research used a descriptive quantitative design with a cross-sectional approach. The sample consisted of 58 elderly individuals selected using a total sampling technique. The instrument used was the Morse Fall Scale to assess the level of fall risk. Data were analyzed univariately and presented in the form of frequency distributions and percentages. The results showed that most of the elderly had a high risk of falling, totaling 43 respondents (74.13%), while 15 respondents (25.86%) had a moderate risk of falling. The factors contributing to a higher risk of falls included muscle weakness, balance disorders, the use of walking aids, and a history of previous falls. In conclusion, the majority of elderly individuals at the Budi Luhur Social Institution in Jambi City had a high risk of falling. Preventive efforts such as physical exercises to improve strength and balance, fall prevention education, and creating a safe environment are necessary to reduce the risk of falls among the elderly.